Javno financiranje vjerskih zajednica i građanska prava u pluralnom i pluralističkom društvu - Bulat, Damir (Array, 2019)
This paper initiates discussion on public (state / local) financing of religious groups. The impression is that it is not in their interest. The relationship between humanistic – lay constitutional directives is considered together with domestic and international contracts of state and religion. Taking these relations into consideration is founded on the presumption according to which state simultaneously protects plurality, freedom of religion, beliefs and conscious, and the dignity of humankind from which freedom of choice emerges. Also considered is from which of its institutions and authority religious groups are separated. One should not, with the same contract, create a relationship which destroys or makes subservient a part of constitutionally guaranteed citizen rights. The state model of financing religious groups from the state budget indicates an ethical and legal paradox because the government with one doctrine of identity uncovers several possibilities of legal involution of parts of fundamental and citizen rights. Such a contract indicates a disharmony of the constitution with the utilitarianism of co/managing non-confrontation.